Response to New Zealand's agricultural sector from economic growth and free trade in China : a computable general equilibrium analysis : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Economics at Massey University, Palmerston North, New Zealand - Wallace, Michael John; Wallace, Michael John (Massey University, 2011)
China’s growth performance over the last three decades has stood at a phenomenal nine percent per annum and shows little sign of abating despite challenging market conditions in recent times. With ever increasing demand and limited land availability this is set to have an increasing impact on New Zealand which has a comparative advantage in land-intensive agricultural products. Already this is observable in recent trade statistics. Using GTAP (global trade analysis project), a computable general equilibrium model, this research estimates the future effects of Chinese growth to New Zealand’s agricultural sectors and its economy in general. Almost all primary industries in New Zealand can expect to benefit from China’s growth, most notably wool and forestry. Modest gains in gross domestic product and economic welfare also benefit the country on the whole. Chinese growth also complements the well documented gains of the recently signed free trade agreement between the two nations.
Keywords: Chinese economy; Free trade; Agricultural industry; Trade agreement; Economic growth